The New National Quality Framework: quantifying some of the effects on labour supply, child care demand and household finances for two-parent households - Trott, Declan; Breunig, Robert; Gong, Xiaodong (My University, 2012)
New regulations to improve the quality of early childhood education and care came into force in Australia in 2012. Using a simultaneous, structural model of labour supply and child care demand we predict the effects on the labour supply of partnered women, on demand for child care and on household finances for two-parent households in Australia. Using estimated cost impacts of this new National Quality Framework from government and non-government sources, we find modest effects on household behaviour. For a mid-range cost scenario, we find that partnered women’s labour force participation will decrease by just over one half of one percentage point, a change of less than one percent. Working hours for partnered women decrease by 20 minutes or about 2 per cent. Household disposable income decreases by $12.50, a 0.6 per cent decrease. Given widespread agreement about the benefits of investing in children, these quantitatively small effects for two-parent households strengthen the case for the National Quality Framework.
Economic Record
Keywords: Education and Training -- Early Childhood; Child Care; Income & Finance -- Financial Management (inc Budgeting); Employment -- Labour force participation; Income, wealth and finances; Labour market; Learning, education and training; Employment; Income & Finance; Child Care; Education and Training; Labour force participation; Financial Management (inc Budgeting); Early Childhood; Income, wealth and finances; Learning, education and training; Employment and unemployment